OPTIMALISASI KURIKULUM PESANTREN DALAM MENINGKATKAN SUMBER DAYA SANTRI DI PONDOK PESANTREN AL-HAMID MAN 1 MALANG - zainuddin fanani (Jurnal Penelitian Ilmiah INTAJ, 2023)
Islamic boarding schools as one of the forms of outside education providers Schools have the potential, position and role which are very important and strategic for creating high-quality human resources. This study aims to analyze and found out about optimizing the pesantren curriculum in improving the student resources of Al-Hamid Islamic Boarding School MAN 1 Malang. It uses qualitative research with a case study type. Technique data collection was carried out by in-depth interviews, participant observation, anddocumentation. The data is analyzed with an interactive model consisting of data collection, data reduction, data presentation and conclusion. The results of this study indicate that curriculum optimatization in Al-Hamid Islamic Boarding School MAN 1 Malang consists: planning refers to the vision, mission, designing the curriculum from the previous year's evaluation; implementing the vision, mission, and refers to the plans that have been made; evaluation that held at the end of each year lessons, making plans for the following year.